In: Advanced Math
Show the following identities for a, b, c ∈ N.
(a) gcd(ca, cb) = c gcd(a, b) Hint: To show that two integers x, y ∈ Z are equal you can show that both x | y and y | x which implies x = y or x = −y. Thus, if both x and y have the same sign, they must be equal.
(b) lcm(ca, cb) = c lcm(a, b)
(c) ab = lcm(a, b) gcd(a, b) Hint: Consider first the case that gcd(a, b) = 1 and show that ab = lcm(a, b) in this case. For the general case combine this with (b).
(d) lcm(gcd(a, c), gcd(b, c)) = gcd(lcm(a, b), c) Hint: First treat the special case that gcd(a, b, c) = 1. In this case begin by showing that lcm(gcd(a, c), gcd(b, c)) = gcd(a, c) gcd(b, c). The asserted equality gcd(a, c) gcd(b, c) = gcd(lcm(a, b), c) is then shown by proving that gcd(a, c) gcd(b, c)| gcd(lcm(a, b), c) and gcd(lcm(a, b), c)| gcd(a, c) gcd(b, c). Proceed to show that gcd(a, c)| lcm(a, b) and gcd(a, c)| c, and deduce from this that gcd(a, c)| gcd(lcm(a, b), c); proceed analogously for gcd(b, c). Then argue that gcd(a, c) gcd(b, c)| gcd(lcm(a, b), c) under the present assumption. Conversely, in order to show that gcd(lcm(a, b), c)| gcd(a, c) gcd(b, c), write according to (a) gcd(a, c) gcd(b, c) = gcd(gcd(a, c)b, gcd(a, c)c) = gcd(gcd(ab, bc), gcd(ac, c2 )), and show that gcd(lcm(a, b), c) divides all of ab, bc, ac, and c 2 . Explain from here why gcd(lcm(a, b), c) must divide gcd(a, c) gcd(b, c) then as well. For the general case explain how (a) and (b) can be used to reduce the general assertion to the previously treated special case.
***The only help I really need is with c and d. I just added a and b for context.